Anatomical and Histological Features in Muscles of Wild Boar (Sus scrofa) from Timor Island - maha, Inggrid Trinidad; AMALO, FILPHIN ADOLFIN; NITBANI, HENY; SELAN, YULFIA NELLYMALIK; jacob, jois; odung, Elisabeth Memot (Acta VETERINARIA Indonesiana, 2025)
The anatomical features and histology of wild boars serve as two parameters for assessing the quality of wild boar meat. This study aimed to identify the anatomical and histological characteristics of wild boar muscles (Sus scrofa) from Timor Island, with potential benefits for the community and veterinary students. The research samples were the longissimus dorsi and biceps femoris muscles from three wild boars slaughtered in the laboratory. Muscle samples were prepared for anatomical observations. Muscle samples were anatomically observed, fixed in 10% alcohol, and then prepared for histological analysis using Hematoxylin and Eosin (HE) staining. The anatomical observation indicated that the boar's muscles exhibited a blackish-red coloration. The longissimus dorsi muscles had a chewy consistency, while the biceps femoris muscles were also chewy, displaying slight density and the distinctive aroma of fresh meat. Histological images indicated that muscle fibers appeared polygonal in shape in transverse sections, while elongated in longitudinal sections. Some fasciculi composed of muscle fibers exhibited multiple nuclei located at their peripheries. Between the muscle fibers, round fat cells with a nucleus were surrounded by three types of connective tissue. The histological characteristics of wild boar exhibit similarities to those of the Timor pig, Sumatran Ongole cattle, and Bali cattle.